Strangers and Neighbours : Rural Migration in Eighteenth-Century Northern Burgundy - Hayhoe, Jeremy (Book collections on Project MUSE., 2016)
In this book, Hayhoe paints a picture of a surprisingly mobile and dynamic Burgundian rural population.